2023
DOI: 10.1172/jci.insight.158077
|View full text |Cite
|
Sign up to set email alerts
|

Sorting nexin 10 sustains PDGF receptor signaling in glioblastoma stem cells via endosomal protein sorting

Abstract: Glioblastoma is the most malignant primary brain tumor for which the prognosis remains dismal even with aggressive surgical, medical, and radiation therapies. Glioblastoma stem cells (GSCs) promote therapeutic resistance and cellular heterogeneity due to their self-renewal properties and capacity for plasticity. To understand the molecular processes essential for maintaining GSCs, we performed an integrative analysis comparing active enhancer landscapes, transcriptional profiles, and functional genomics profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 77 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…Accumulating studies have shown the association of SNX10 and multiple cancers, such as colorectal cancer (Le et al., 2018; Zhang, Yang, et al., 2020) and glioblastoma (Gimple et al., 2023). However, it is not clear whether SNX10 has been implicated in gastric cancer as well.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Accumulating studies have shown the association of SNX10 and multiple cancers, such as colorectal cancer (Le et al., 2018; Zhang, Yang, et al., 2020) and glioblastoma (Gimple et al., 2023). However, it is not clear whether SNX10 has been implicated in gastric cancer as well.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, AGS cells treated with 4.0 mM Rop were used in the subsequent experiments. SNX10 deficiency has been reported to be associated with proliferation of colorectal cancer (Le et al., 2018; Zhang, Yang, et al., 2020) and glioblastoma (Gimple et al., 2023). Whether SNX10 is involved in the Rop‐induced inhibitory effect on the proliferation of gastric cancer cells remains unclear.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…IL8 [11] Mixed effect: SNX10 [14,23] MARS, CHI3L1 [45,43] RANBP17 [45] M-effect: JMJD1A, OLIG2 [3] CBR1 [22] FPRL1 [26] SYTL2 [9] P2RY6, CCR1 [34] TLR2 [36] F3 [13] SECTM1 [35] GPRC5A [48] PIP4K2C [1] APOC2 [27] TKTL1 [16] ZNF135, PCYOX1 [8] LSP1, ZCCHC2, HPGD [31] Note: Those without citations are new genes needed to be further studied. of RANBP17, CHI3L1, and SNX10 are with prognosis of GBM and their methylation status are suggested to play an important role in GBM or other cancer.…”
Section: M-effectmentioning
confidence: 99%